VERB SYSTEM OF KOSOVO METOHIJA DIALECTS OF KOSOVO RESAVA TYPE (Heritage, 2026)
The paper work has analyzed selected morph syntactic details of verbs (present, aorist imperfect, future 1, infinitive, imperative, adverbial verb) in dialects of Donja Sitnica (Banjska and Gojbulja) and Middle Ibar (Isevo and Socanica), which belong to south subdialect of Kosovo Resava dialect. General conclusion is that condition in researched zones is mostly balanced, which means that diasystems have two distant zones of stable Kosovo Resava properties, but also there is indulgence of structures and tendencies towards expansion of innovations of Balkan type in speeches of Donja Sitnica, which are still in their infancy and their justification is in positioning this zone towards lingvogeographic periphery. Innovative features did not affect the morph syntactic level to a large extent, which testifies to the inclusion of this area in the all stokavian flows of Kopaonik belt.
Keywords: verb system, morph syntactic aspect, Donja Sitnica, Srednji Ibar, Kosovo Resava dialect, south sub dialect, Kosovo Metohija dialects, lingual geographic periphery.